Analisis Kemampuan Interaksi Sosial pada Anak Retardasi Mental - Natalia Devi Oktarina; Fiki Wijayanti; Wahyu Ningtyas Handayani (STIKes Santa Elisabeth Medan, 2023)
Introduction : Mentally retarded children often experience difficulties in interacting socially with other people due to intellectual limitations and self-adjustment, in addition to environmental factors such as family support. This study aims to analyze the social interaction abilities of mentally retarded children at the Ungaran State Special School (SLBN). Method : This type of research is a descriptive study to analyze social interaction skills in mentally retarded children. The sampling technique used was Total Sampling with a sample of 52 students. The measuring tool for this study used a questionnaire, namely a questionnaire that had previously been tested for validity. Data analysis used the Spearman Rank test.Result : Children with mental retardation in State Special Schools (SLBN) have the ability to social interaction mostly in the good category (53.8%).Conclusion : Sosial interaction children with mental retardation in good category, parents and schools can continue to provide stimulus to children so that social interaction in children with mental retardation can develop properly.